Econometric assessment of the role of the pace of life in the socio-economic development of the region - Karpenka, Elena M.; Rasseka, Yuliya Yu. (Journal of the Belarusian State University. Economics, 2022)
The author’s methodology for assessing the regional pace of life at the world level has been tested. With the help of statistical analysis tools, its place and role in the system of indicators of socio-economic development of a number of countries are studied. The construction of an econometric model allowed us to establish the influence of factors of demographic, economic, natural-climatic and national-cultural groups on the magnitude and dynamics of the regional pace of life, which formalises its dependence on these factors and provides an opportunity to apply the constructed model in practice in the management process.
Keywords: regional pace of life; correlation and regression analysis; system of indicators; econometric model; factors of influence